Developing Students' Critical Thinking by Using Problem Based Instruction Strategy - Elyza Martiarini (Scope : Journal of English Language Teaching, 2017)
The objective of this research was to obtain an empirical data about developing students’ critical thinking by using problem based instruction strategy. The method of this research was experimental study and conducted upon 60 students of fourth semester of English Department at University of Indraprasta PGRI in 2015-2016 academic year. The instrument tests were firstly tried out to determine the validity and reliability. Hypothesis testing techniques performed by ttest, and obtained a value of 6,012 with significance level ? = 0,95%, while the ttable was 1,701. Thus, it seen that ttest was higher than ttable, the hypothesis null (H0) was rejected and research hypothesis (H1) was accepted. So, it can be concluded that developing students' critical thinking by using problem based instruction strategy was significant.